Food consumers' views of essential food knowledge and skills for all consumers. Issue 3 (3rd April 2018) - Burton, Melissa; Riddell, Lynn; Worsley, Anthony
Abstract : Purpose: Food education in secondary schools can provide adolescents with essential food knowledge and skills required for healthy, independent living. The purpose of this paper is to identify food-related knowledge and skills that Australian consumers believe are required for all consumers, and to identify their demographic and psychographic associations based on two studies. Design/methodology/approach: Two online surveys were conducted in 2012 and 2014 in different samples of Australian consumers ( n =2, 146 and 770, respectively), both drawn from a commercial research panel. Respondents rated their views on the importance of food knowledge and skills items as "essential" or "not essential" in the 2012 survey, or by rating their importance in the 2014 using five-point scales. Principal components analysis, confirmatory factor analysis and stepwise multiple regression analysis were used to group the different types of food knowledge and skills and identify their associations. Findings: In both surveys, "the effects of food on people's health" and "how to prepare food safely" were viewed as the most important knowledge and skills, and food production, food system and environmental items were the least important. Food knowledge and equality values were positively associated with the importance of Nutrition Knowledge and Practical Skills in both surveys. In addition, food mavenism was a positive predictor of Nutrition and Health Knowledge and The Food System in 2012 and female sex was positively associated with Practical Food Skills. Research limitations/implications: Most respondents believed that nutrition and health knowledge and practical food skills were more important than knowledge of food production, the food system or the environment. The findings suggest that psychological factors such as personal values, food knowledge and food mavenism may be more important influences over these perceptions than respondents' demographic characteristics. Originality/value: This research is novel as it explores consumers' views about the food knowledge and skills that all consumers need to be healthy and independent, and has important implications for food education, particularly in secondary schools. In addition, it assessed consumers' views at two different time points, two years apart and, thus, provides evidence for stability of these views.